Calcifying Pseudoneoplasms of the Skull Base Presenting with Cranial Neuropathies: Case Report and Literature Review - Nonaka, Yoichi; Aliabadi, Hamid R.; Friedman, Allan H.; Odere, Fred G.; Fukushima, Takanori (Journal of Neurological Surgery Reports, 2012)
Objectives We report our institutional experience with calcifying pseudoneoplasms of the skull base that presented with cranial neuropathies. These lesions are also known as fibro-osseous lesions, cerebral calculi, or brain stones.Results One patient presented with facial numbness and retro-orbital pain secondary to compression of the maxillary branch of the trigeminal nerve at the anterior portion of the infratemporal fossa. The other patient presented with occipital headaches and hypoglossal nerve palsy. This patient was found to have a calcified lesion in the posterior fossa, which eroded the left occipital condyle.Conclusion Calcifying pseudoneoplasms are benign, slow-growing masses that are apparently cured by gross total resection. Even with incomplete tumor resection, the prognosis is considered to be favorable. We advocate a minimally invasive surgical resection of such tumors involving the cranial nerves.
Keywords: brain stone; calcifying pseudoneoplasm; cerebral calculi; fibro-osseous lesion; neural axis